IMPLEMENTASI QRIS SEBAGAI STRATEGI DIGITALISASI TRANSAKSI UNTUK MENINGKATKAN EFISIENSI PADA UMKM: STUDI KASUS WARUNG MAKAN NYANYU - Phatra Anggana Djuri; Andi Nur Ram Shafira; Erwinsyah; Femilia Zahra (Jurnal Nusa Manajemen, 2026)
Digital transformation is essential for Micro, Small, and Medium Enterprises (MSMEs) to improve efficiency and competitiveness. The Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia, unifies multiple digital payment codes into a single national standard. This study aims to describe the implementation of QRIS at Warung Makan Nyanyu in Palu City, focusing on efficiency benefits, challenges, and adaptation strategies. A qualitative case study was employed, using semi-structured interviews, direct observation, and transaction documentation. The findings reveal that QRIS enhances transaction speed, provides automatic recording that reduces manual errors, and minimizes risks associated with cash handling. However, challenges include unstable internet connectivity, low digital literacy among some customers, and the burden of the Merchant Discount Rate (MDR). Strategies adopted include providing backup data packages, educating customers, and offering digital payment discounts. The study highlights QRIS as not only a payment tool but also a vital instrument for MSME digital transformation and financial inclusion.